Entry Costs and the Macroeconomy - Gutierrez, German (IMF Working Papers; Working Paper ;, 2019)
We combine a structural model with cross-sectional micro data to identify the causes and consequences of rising concentration in the US economy. Using asset prices and industry data, we estimate realized and anticipated shocks that drive entry and concentration. We validate our approach by showing that the model-implied entry shocks correlate with independently constructed measures of entry regulations and M and As. We conclude that entry costs have risen in the U.S. over the past 20 years and have depressed capital and consumption by about seven percent.